Illumination angle and layer thickness influence on the photo current generation in organic solar cells: A combined simulative and experimental study - Jan Mescher; Adrian Mertens; Amos Egel; Siegfried W. Kettlitz; Uli Lemmer; Alexander Colsmann (AIP Advances, 2015)
In most future organic photovoltaic applications, such as fixed roof installations, facade or clothing integration, the solar cells will face the sun under varying angles. By a combined simulative and experimental study, we investigate the mutual interdependencies of the angle of light incidence, the absorber layer thickness and the photon harvesting efficiency within a typical organic photovoltaic device. For thin absorber layers, we find a steady decrease of the effective photocurrent towards increasing angles. For 90-140 nm thick absorber layers, however, we observe an effective photocurrent enhancement, exhibiting a maximum yield at angles of incidence of about 50°. Both effects mainly originate from the angle-dependent spatial broadening of the optical interference pattern inside the solar cell and a shift of the absorption maximum away from the metal electrode.